Tupelo rides the rails - Sweet, Melissa, 1956- (Houghton Mifflin Company, 2008)
After being left by the side of a road with nothing but her favorite sock toy, Tupelo meets a pack of dogs led by Garbage Pail Tex as they are wishing for new homes, then joins them as they catch a passing train and share stories of dog heroes.